PERFORMA PENGGUNAAN KOSAKATA OLEH GUBERNUR DAN WAKIL GUBERNUR SUMATERA BARAT DI DALAM YOUTUBE - Anggrina, Silvia; Ermanto, Ermanto; Emidar, Emidar (Universitas Negeri Padang, 2018)
This study aims to describe the performance of using Indonesian vocabulary in terms of using the principle of language vocabulary by the governor and vice governor of West Sumatra on Youtube. This study is a qualitative research using descriptive method. The study data are speech by the governor and vice governor of West Sumatra. The data were collected in the following manner, (1) the author download the video of the governor and vice governor of West Sumatra in social media, Youtube; (2) the author transcribes the entire Youtube video; and (3) the author observe and determine data that includes the performance of Indonesian vocabulary; (4) the author include the code to performance of using Indonesian vocabulary. After the data collected, then the author is analyzing the data with the following steps, (1) identifying and transcribing data, (2) classifying data, (3) calculating data, (4) interpreting data, and (5) summing up data. The conclusion of the study is the performance of Indonesian vocabulary in the speech of the governor and vice governor of West Sumatra in well phase. The author found 76% data using standard vocabulary and 24% data using non standard vocabulary. If the data explained in number, the using of standard vocabulary is 276 sentences and non standard vocabulary is 86 sentences.Keywords: vocabulary, governor and vice governor, Youtube